Strategi Guru Bahasa Arab Dalam Meningkatkan Kosa-Kata Bahasa Arab Di SMP IT Al-Jawahir - Safira, Ervina Rahma (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research aims to determine the strategies of Arabic teachers increasing Arabic vocabulary at SMP IT Al-Jawahir. The method used In this research is a qualitative research method. This research use 2 types of data sources, namely primary data and secondary data. In collecting primary data, researchers take data directly from informants through interview, observation, and documentation techniques. The data analysis techniques used by researchers are Data Reduction, Data Display, and Conclusion/Verification techniques.The result of this research are that there are 2 teacher strategies in learning Arabic vocabulary at Al-Jawahir IT Middle School, namely the Educational Game Strategy and the Arabic Vocabulary Singing Strategy. With the Educational Game Strategy, students can easilly understand Arabic, both through pictures and Arabic writing. And with the Singing Strategy in learning vocabulary, student can memorize vocabulary quickly. Supporting factors In the learning strategiles carried out by teachers at SMP IT Al-Jawahir are professional Arabic teachers, the availability of learning facilities, and student’s interest In learning. The inhibiting factors for learning strategies are the background of students who come from general Elementary School (SD), the background characteristics of each student, an environment that does not use Arabic, and short learning time.